2016
DOI: 10.15436/2378-6841.16.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Hardness on Non-Communicable Diseases, Including Chronic Kidney Disease of Multifactorial Origin (CKDmfo/CKDuo)

Abstract: Environmental pollution, including air and water contamination, causes or aggravates many acute and chronic human diseases. Although scientific literature prior to the last decade showed some associations between hardness/softness of water with cardiovascular diseases, recent data do not support this proposition. Previously postulated associations were derived from the data generated from observations and uncontrolled epidemiological and cohort studies; the results of which have not been confirmed. It was clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Jayasumana et al (2014), reported high water hardness (up to 820 mg/L) in CKDu endemic areas which showed a correlation with the prevalence of CKDu [3,18]. But, unexpected low occurrence of CKDu was found in Jaffna and Puttalam districts even with reported higher water hardness (approximately 1500 mg/L) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Jayasumana et al (2014), reported high water hardness (up to 820 mg/L) in CKDu endemic areas which showed a correlation with the prevalence of CKDu [3,18]. But, unexpected low occurrence of CKDu was found in Jaffna and Puttalam districts even with reported higher water hardness (approximately 1500 mg/L) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle changes needed in the said population include, consuming a nutritionally balanced diet, engaging in age-appropriate physical activities, and avoiding smoking, alcohol, and illicit drugs. In addition to CKD, these would also reduce the risks of other chronic diseases, such as type 2 diabetes, metabolic syndrome, obesity, and osteoporosis [35, 36].…”
Section: Resultsmentioning
confidence: 99%
“…The origin (the causation) of CKDmfo is multifactorial. Poverty-driven malnutrition, unhealthy lifestyles and habits, excessive use of agrochemicals, and ineffective governmental policies, all can be intricately interconnected [16, 35]. These factors likely to make individuals vulnerable, while chronic and prolonged ingestion of nephrotoxins contribute to precipitate CKDmfo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also echoes the findings of research in Dhaka, Bangladesh reporting that the total microbial count in household waste collectors was about 20,000 times higher than in general [ 45 ]. The scarcity of clean drinking water also creates abdominal pains and gastrointestinal problems [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%